1997
DOI: 10.7557/2.17.2.1303
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-slaughter selection of reindeer bulls (Rangifer tarandus tarandus L.) on technological and sensory meat quality, blood metabolites and abomasal lesions

Abstract: Thirty reindeer bulls (age Vh years) were subjected to different pre-slaughter treatments to study the effects on ultimate pH values, muscle glycogen content, blood metabolites and abomasal lesions. Gathering and herding inro a grazing corral were followed by various selection procedures. Before starting these, a control group of 10 reindeer were captured by lasso and slaughtered outside the gtazing corral. Ten reindeer were then selected by hand from a small group of animals (100-150 head) in a small selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In the present material, abomasal lesions were superficial, and appeared acute. This type of lesions is a relatively common finding in reindeer, and its relation to stress is well documented [ 22 - 24 ]. This is consistent with our findings, as there was no association between abomasal lesions and other factors that we controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In the present material, abomasal lesions were superficial, and appeared acute. This type of lesions is a relatively common finding in reindeer, and its relation to stress is well documented [ 22 - 24 ]. This is consistent with our findings, as there was no association between abomasal lesions and other factors that we controlled.…”
Section: Discussionmentioning
confidence: 99%
“…A so-called 'stress flavour' has been found in meat from intensively pre-slaughter handled reindeer (Hanssen et al, 1984;Wiklund et al, 1996bWiklund et al, , 1997, but the phenomenon has not been described or explained chemically (Rehbinder & Edqvist, 1981;Rogstadkjaernet & Hanssen, 1985;Hanssen & Skei, 1990). Brooks & Collins (1984) showed that the meat from reindeer in poor physical condition had an 'undesirable' flavour.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the different pre-slaughter handling routines (reindeer: Wiklund, Malmfors, Lundström, & Rehbinder, 1996;Wiklund, Malmfors, & Lundströ m, 1997), transport (reindeer: Wiklund, Andersson, Malmfors, Lundströ m, & Danell, 1995;Wiklund, Rehbinder, Malmfors, Hansson, & Danielsson-Tham, 2001a; red deer and fallow deer: Pollard, Stevenson-Barry, & Littlejohn, 1999) and lairage (red deer: MacDougall et al, 1979;Pollard et al, 1999;reindeer: Wiklund, Andersson, Malmfors, & Lundströ m, 1996) on various of the physical meat quality attributes has been reported and reviewed Renecker et al, 2001;Wiklund & Malmfors, 2004). As a conclusion of all these studies, possibilities to improve pre-slaughter handling routines for all deer species included were identified which would further reduce the frequency of DFD (Dark, Firm, Dry) meat with high ultimate pH values.…”
Section: Deermentioning
confidence: 99%